Sustainable Harvesting of Nagarmotha (Cyperus scariosus R. Br.) - Rani, Abha; Chawhaan, Pravin H.; Rathore, Mala (Indian Forester, 2009)
Nagarmotha (Cyperus scariosus R. Br.) is the most important locally available minor forest produce resource of Chhattisgarh and a significant contributor in the revenue of Minor Forest Produce Co-operative Federation Limited., Chhattisgarh. Due to its unsustainable over exploitation it is under threat of depletion. Keeping this in view the present investigation was conducted at Kajool nadi and Bhabaarganj nadi, Dhugli Range, Dhamtari District, Chhattisgarh to know the effect of harvesting intensity on regeneration/ multiplication status of this species. The study area consists of four plots each randomly allotted to four different harvesting intensities (treatments) viz. 60%, 70%, 80% and 90% harvest. In each plot total growing plant population were counted, thereafter as per the allotment 60%, 70%, 80% and 90% plants were uprooted from the whole plot. From the harvested tillers rhizomes were removed, cut into small pieces and essential oil was extracted by steam distillation and yield of the oil was quantified (0.04âˆ’0.07%). The whole experiment was reassessed in the month of December 2006 and total Nagarmotha plants in each plot were again counted and the data so obtained was then subjected to analysis of variance. Conclusively from the experiment it was inferred that for the sustainable harvesting 80% to 90% population of Nagarmotha should only be harvested uniformly from the whole plot to ensure proper regeneration.